Law Responsible in the Development of Local Rules on the Tourism Health in Magelang City - Suwandoko, Suwandoko; Winanta, Rizza Arge; Perdana, Bonifasius Endo Gauh; Hardyati, Desty Puteri Hardyati; Kusuma , Trisma Arindhita (Universitas Negeri Semarang, 2024)
The right to health in tourism places is very necessary to guarantee the right to health for tourists. Health insurance at tourist attractions aims to prevent and overcome unexpected events that will have a negative impact on tourists' health. Tourism management in Magelang City does not have regulations related to tourism health. So, the Magelang City Government needs to prepare regional regulations regarding health tourism, which have a responsive legal character, namely according to community needs and there is community participation in every drafting process. This research aims to analyze the urgency of forming regional regulations on tourism health in Magelang City and the role of responsive law in forming regional regulations on tourism health in Magelang City. The type of research is empirical juridical research, the data sources are primary data and secondary data, the data analysis technique is the interaction analysis model. Research results the urgency of forming regional regulations regarding tourism health in Magelang City is in line with the right to health at tourist attractions based on philosophical, sociological and juridical aspects to guarantee the right to health for tourists, the community around tourist attractions, and tourist attraction managers. The role of responsive law in the formation of regional regulations on tourism health in Magelang City refers to the importance of the community participating in the formation of regional regulations on tourism health, in which case the regional regulations formed have a responsive character.